Effect of arrangements in an atmospheric hydrotreating reactor of cobalt and/or molybdenum dispersed on activated carbon catalysts toward bio-jet fuel production from refined palm oil - Ady Yulianto; Wega Trisunaryanti; Triyono Triyono; Aldino Javier Saviola; Karna Wijaya; Indriana Kartini; Suryo Purwono; Rodiansono Rodiansono; Ady Mara (Case Studies in Chemical and Environmental Engineering)
The issue of the depletion of the availability of fossil fuels for the aviation industry and the adverse effects of their use has led researchers to continue to develop biofuels from vegetable oils that are abundant in nature. This research successfully converted refined palm oil (RPO) into bio-jet fuel catalyzed by Co and/or Mo dispersed on activated carbon at atmospheric pressure. The catalyst materials were synthesized using the spray impregnation method. Various monometal and/or bimetal catalyst arrangements in the reactor were tested for their performance in the hydrotreatment process, primarily to assess the role of molybdenum as an active metal for hydrodeoxygenation reaction. The Co/C (top) coupled with Mo/C (bottom) catalyst arrangement produced the highest bio-jet fuel yield of 49.8 % with a selectivity of 94.59 % using RPO feed that had undergone thermal treatment at 450–550 °C. Compared to other studies, this research can produce bio-jet fuel with much lower pressure, thus making it greener and safer.